Kontribusi Bank Sampah Terhadap Pemberdayaan Masyarakat Gampong Blang Krueng Aceh - Wildan - Mukhtari; Samhudi - Samhudi; Maturidi - Maturidi (Empower : Jurnal Pengembangan Masyarakat Islam, 2022)
This study aims to determine how the waste management system in the waste bank of Gampong Blang Krueng and how the contribution of the waste bank to community empowerment in Gampong Blang Krueng. This research is a qualitative research, the method used in this research is descriptive, the aim is to provide a clear picture of the state of the object under study based on the facts that appear as they are. The data collection techniques in this study used, observation, interviews and documentation. The results showed that the contribution of the waste bank to community empowerment was divided into two aspects, namely the aspect of building public awareness and the aspect of empowering the productive economy of the community. The first aspect is to build public awareness in managing waste. The second aspect is empowering productive economic communities, which means managing waste that can be recycled and then producing goods of value for resale.